2021
DOI: 10.3390/brainsci11121577
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ma2 Antibody-Associated Paraneoplastic Neurological Syndromes: A Pilot Study

Abstract: Paraneoplastic neurologic syndromes (PNSs) are a heterogeneous group of disorders caused by the remote effects of cancer with immune-mediated pathogenesis. Anti-Ma2 antibody was defined as one of the well-characterized onconeural antibodies that could help establish a definite PNS diagnosis. We aimed to report and explore patients with anti-Ma2 antibody-associated paraneoplastic neurologic syndrome (Ma2-PNS) who frequently exhibit sensorimotor neuropathy (SMN) using a new method of factor analysis of mixed dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Ma2 is a class of rare onconeural antibodies mostly associated with testicular, lung, and gastrointestinal tumors 82 . Previous studies have shown that Ma2‐paraneoplastic neurologic syndromes (PNS) has a high mortality rate and poor prognosis even after tumor treatment and immunosuppressive therapy 8 . This article inductively collects analytically agree with the view.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Ma2 is a class of rare onconeural antibodies mostly associated with testicular, lung, and gastrointestinal tumors 82 . Previous studies have shown that Ma2‐paraneoplastic neurologic syndromes (PNS) has a high mortality rate and poor prognosis even after tumor treatment and immunosuppressive therapy 8 . This article inductively collects analytically agree with the view.…”
Section: Discussionmentioning
confidence: 65%
“… 82 Previous studies have shown that Ma2‐paraneoplastic neurologic syndromes (PNS) has a high mortality rate and poor prognosis even after tumor treatment and immunosuppressive therapy. 8 This article inductively collects analytically agree with the view. However, due to too few cases, inductive bias may exist, which needs to be verified by further prospective studies.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…PNSs with peripheral nerve damage are extremely rare compared with the well-characterized limbic encephalitis and paraneoplastic cerebellar degeneration; further, they are difficult to differentiate from typical peripheral neuropathy. Most of the current case analyses have focused on the clinical and electrophysiological features of typical syndromes with specific antibodies [ 6 , 7 , 8 ], tumor types [ 9 ], or rare case reports [ 10 , 11 ]. However, paraneoplastic neuropathy clinically occurs with extensive variation in the progression of the neuropathy; its pattern; the degree of sensory, motor, and autonomic involvement; and the presence or absence of paraneoplastic autoantibodies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%